2016
DOI: 10.3945/ajcn.116.139519
|View full text |Cite
|
Sign up to set email alerts
|

Moderate folic acid supplementation and MTHFD1-synthetase deficiency in mice, a model for the R653Q variant, result in embryonic defects and abnormal placental development

Abstract: Background: Moderately high folic acid intake in pregnant women has led to concerns about deleterious effects on the mother and fetus. Common polymorphisms in folate genes, such as methylenetetrahydrofolate dehydrogenase-methenyltetrahydrofolate cyclohydrolaseformyltetrahydrofolate synthetase (MTHFD1) R653Q, may modulate the effects of elevated folic acid intake. Objectives: We investigated the effects of moderate folic acid supplementation on reproductive outcomes and assessed the potential interaction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…The present study found that chronic FS could actually influence the lipid metabolic process by influencing glycerophospholipid metabolism, glycerolipid metabolism and fatty acid biosynthesis. However, the hepatic TG contents were increased in the breeder cocks and their offspring from the PFS groups, which was in accordance with previous studies [26,27]. Additionally, enhanced glucose metabolic functions, especially glycolysis and gluconeogenesis functions, were identified in breeder cocks and their offspring from the FS groups.…”
Section: Results and Discussion (A) Phenotypic Changes In Breeder Cocsupporting
confidence: 91%
See 1 more Smart Citation
“…The present study found that chronic FS could actually influence the lipid metabolic process by influencing glycerophospholipid metabolism, glycerolipid metabolism and fatty acid biosynthesis. However, the hepatic TG contents were increased in the breeder cocks and their offspring from the PFS groups, which was in accordance with previous studies [26,27]. Additionally, enhanced glucose metabolic functions, especially glycolysis and gluconeogenesis functions, were identified in breeder cocks and their offspring from the FS groups.…”
Section: Results and Discussion (A) Phenotypic Changes In Breeder Cocsupporting
confidence: 91%
“…Previous studies have mostly shown that folate could promote lipoclastic activity by increasing the biosynthesis of phosphatidylcholine and carnitine and by decreasing the expression of lipid synthesis-related genes [11]. However, several recent studies have found that chronic FS could induce increased inactive folate in the body and further induce lipopexia in the liver [26,27]. The present study found that chronic FS could actually influence the lipid metabolic process by influencing glycerophospholipid metabolism, glycerolipid metabolism and fatty acid biosynthesis.…”
Section: Results and Discussion (A) Phenotypic Changes In Breeder Cocmentioning
confidence: 43%
“…A study reported by Rozen’s group has also shown that the lack of MTHFDA synthetase significantly affects embryonic defects in female mice. The study demonstrated that disruption of the maternal MTHFD1 gene damages fetal growth [ 86 ]. There are also ample studies that suggest ANXA2 is closely involved with embryo implantation and breast cancer, by acting as an adhesion molecule on the endometrium [ 87 , 88 , 89 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another likely possibility is that the fetal underdevelopment is a result of other components in the 1C imbalanced diet. Excess folate alone has previously been shown to cause placental abnormalities and embryonic defects in mice [ 20 , 21 ]. In addition, low B12 combined with high folate may exacerbate B12 deficiency [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%